1354 Measuring airborne exposure of french farmers during work related to livestock and to harvesting of various crops: the airexpa project. (24th April 2018) - Boulanger, M; Bouchart, V; Lecluse, Y; Pons, R; Clin, B; Baldi, I; Lebailly, P; Tual, S
Abstract : Introduction: Beyond pesticide exposure, farmers are likely to be exposed to several air pollutants. Some of them are of particular interest, either because of their known carcinogenic properties, for lung cancer (total dust, Diesel exhaust, crystalline silica, ) or other cancer sites (mycotoxins) or because of a supposed protective effect on lung cancer risk (endotoxins). However, except for endotoxins, very few studies, assessed farmers' exposure levels by individual samplings. Our study aims at describing the levels, and assessing the determinants, of agricultural exposure to these air pollutants. Methods: We assessed French farmers' individual exposure to several air contaminants: (1) inhalable endotoxins and mycotoxins during various tasks in several breedings (cattle, horse) and 3 crops (grassland, wheat/barley, peas); (2) respirable crystalline silica during harvesting of these 3 crops; (3) respirable elementary carbon during the use of Dieselized farm equipment. Inhalable dusts, up to 20 µ, were assessed in real time. Sampling was performed during the whole activity, and endotoxin exposure was also assessed for each task separately. Field monitors followed the farmers and collected detailed information on the activity. Results: The field study is on-going, we already observed around 40 individual measurements in 20 different farms. The protocol was judged acceptable by the participants. Sampling duration ranges from 80 to 240 min, depending on the type of activity. First results from real-time dust measurements suggest a higher exposure during stables cleaning and mulching (mean concentration of inhalable dusts: 0.545 mg/m 3 ). A total of several hundreds of measurements is expected in various types of farms and working conditions (number of animals, cultivated area, type of equipment). Discussion: We hope our study will improve the assessment of occupational health hazards in agriculture, and thus primary prevention, by quantifying the levels of individual exposure to several air pollutants.